2017
DOI: 10.1038/srep43837
|View full text |Cite
|
Sign up to set email alerts
|

Vlasouliolides A-D, four rare C17/C15 sesquiterpene lactone dimers with potential anti-inflammatory activity from Vladimiria souliei

Abstract: Vlasouliolides A-D (1–4), four rare sesquiterpene lactone dimers, were isolated from Vladimiria souliei. The common structural characteristic of 1–4 is the C32 skeleton comprising two sesquiterpene lactone units linked by a C11-C13′ single bond with one acetyl connected to the C-13 position of one of the two sesquiterpene lactone units. The stereochemistries of 1–4 were assigned by a combination of NOESY correlations and Cu-Κα X-ray crystallographic analyses. Compounds 1–4 strongly inhibited the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…Similar changes were observed for the other vlasouliolides. The spectra of the synthesized vlasouliolides were identical to those reported for the natural products. , …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Similar changes were observed for the other vlasouliolides. The spectra of the synthesized vlasouliolides were identical to those reported for the natural products. , …”
Section: Resultssupporting
confidence: 69%
“…HRMS (ESI) m / z : [M – H] − calcd for C 32 H 39 O 5 505.2959; found 505.2592. NMR data obtained for 13 matches the one reported in the bibliography . NMR data is available in the SI.…”
Section: Methodssupporting
confidence: 67%
“…Dolomiaea is commonly known as "Chuan Mu Xiang" in traditional Chinese medicine (Wei et al, 2014;Huang et al, 2019). Species of Dolomiaea are used medicinally for their significant bioactivities such as antioxidant , anti-inflammatory (Chen et al, 2017;Shi et al, 2017) and antimicrobial (Chen et al, 2015) properties, and are also rich resources of multiple chemical components such as sesquiterpenes (Chen et al, 2015), triterpenes , and phenylpropanoids (Wei et al, 2014). Despite significant medicinal value, genomic resources of Dolomiaea are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Chen reported that vlasouliolides A‐D isolated from Vladimiria souliei , inhibited the production of NO in LPS‐stimulated RAW 264.7 cells. Furthermore, 1–10 μM vlasouliolides A and B inhibited the activation of NF‐κB in LPS‐induced 293 T cells (L. Chen et al, 2017). Shi et al found that 50 and 100 μM alismol reduced NO and PGE 2 levels and suppressed the expression of iNOS and COX‐2 in LPS‐stimulated primary and cultured microglia.…”
Section: Pharmacological Studies Of “Muxiang” Speciesmentioning
confidence: 99%
“…Zhou et al have separated, purified and determined 9‐oxonerolidol ( V36 ), vaernopolyanthone ( V37 ), 15‐acetoxy‐11 α H‐germacra‐1(10) E ,4 E ‐diene‐12,6 α ‐olide ( V38 ), 15‐acetoxy‐11 β H‐germacra‐1(10) E ,4 E ‐diene‐12,6 α ‐olide ( V39 ), 12‐hydroxy‐5 α (H),7 α (H)‐eudesm‐4(14),11(13)‐diene‐9‐one ( V40 ), oplodiol ( V41 ), dihydroestafiatone ( V42 ), 10‐oxodihydroxy‐11 β ,13‐dihydrodehydrocostuslactone ( V43 ), (11 S )‐13‐hydroxylguaia‐4(15),10(14)‐diene‐12,6 α ‐olide ( V44 ) from Vladimiria souliei in 2017 (Zhou, Chen, Li, Zhang, & Wang, 2017). Vlasouliolide A ( V45 ), vlasouliolide B ( V46 ), vlasouliolide C ( V47 ), and vlasouliolide D ( V48 ) were also discovered in 2017 (L. Chen et al, 2017). 25‐Hydroxy‐uvaol ( V49 ) was found in 2019 (Lan et al, 2019; Y.…”
Section: Phytochemistrymentioning
confidence: 99%